An Unprecedented Set of High‐Resolution Earth System Simulations for Understanding Multiscale Interactions in Climate Variability and Change. (1st December 2020) - Chang, Ping; Zhang, Shaoqing; Danabasoglu, Gokhan; Yeager, Stephen G.; Fu, Haohuan; Wang, Hong; Castruccio, Frederic S.; Chen, Yuhu; Edwards, James; Fu, Dan; Jia, Yinglai; Laurindo, Lucas C.; et al.
Abstract: We present an unprecedented set of high‐resolution climate simulations, consisting of a 500‐year pre‐industrial control simulation and a 250‐year historical and future climate simulation from 1850 to 2100. A high‐resolution configuration of the Community Earth System Model version 1.3 (CESM1.3) is used for the simulations with a nominal horizontal resolution of 0.25° for the atmosphere and land models and 0.1° for the ocean and sea‐ice models. At these resolutions, the model permits tropical cyclones and ocean mesoscale eddies, allowing interactions between these synoptic and mesoscale phenomena with large‐scale circulations. An overview of the results from these simulations is provided with a focus on model drift, mean climate, internal modes of variability, representation of the historical and future climates, and extreme events. Comparisons are made to solutions from an identical set of simulations using the standard resolution (nominal 1°) CESM1.3 and to available observations for the historical period to address some key scientific questions concerning the impact and benefit of increasing model horizontal resolution in climate simulations. An emerging prominent feature of the high‐resolution pre‐industrial simulation is the intermittent occurrence of polynyas in the Weddell Sea and its interaction with an Interdecadal Pacific Oscillation. Overall, high‐resolution simulations show significant improvements in representing global mean temperature changes, seasonal cycle of sea‐surface temperature and mixed layer depth, extreme events and in relationships between extreme events and climate modes. Plain Language Summary: Although the current generation of climate models has demonstrated high fidelity in simulating and projecting global temperature change, these models show large uncertainties when it comes to questions concerning how rising global temperatures will impact local weather conditions. This is because the resolution ( 100 km) at which the majority of climate models simulate the climate is not fine enough to resolve these small‐scale regional features. Conducting long‐term (multi‐centuries) high‐resolution ( 10 km) climate simulations has been a great challenge for the research community due to the extremely high computational demands. Through international collaboration, we are able to address this challenge by delivering an unprecedented set of multi‐century high‐resolution climate simulations using the Community Earth System Model (CESM), capable of directly representing tropical cyclones and extreme rainfall events. In this paper, we give an overall assessment of the value and benefit of the high‐resolution CESM climate simulations by making a direct comparison to an identical set of low‐resolution CESM simulations. We showcase some of the major improvements of the high‐resolution CESM in simulating global mean temperature changes, seasonal cycle of sea‐surface temperature, and extreme events, such as tropical cyclones and relationships between tropical cyclones and El Niño‐Southern Oscillation. Key Points: An unprecedented set of multi‐century high‐resolution Community Earth System Model (CESM) simulations is described High‐resolution CESM simulations reveal a potential role of Southern Ocean polynyas in multidecadal climate variability High‐resolution CESM exhibits significantly improved simulations of extreme events, such as tropical cyclones and atmospheric rivers